ANALISIS KEBUTUHAN MAHASISWA TADRIS BIOLOGI UNIVERSITAS ISLAM NEGERI SUMATERA UTARA MEDAN TERHADAP MODUL PRAKTIKUM - Adlini, Miza Nina; Arya, Mhd.; Nasution, Mega Wahyuni; Nurshabirah; Nandhini, Saroza; Agustina, Tri (Transpublika Publisher, 2023)
Education is an initial container for producing high-quality human resources. Practicum is a learning activity aimed at providing students with opportunities to test and apply theories using laboratory facilities and also outside the laboratory. The purpose of this research is to analyze the level of need of biology education students for practicum modules. In conducting this research, the researcher used the Descriptive method with a qualitative approach. The researcher selected 15 Biology students as the sample for this study. The instrument used for the practicum was interviews, where aspects inquired about the importance of modules in practicum and the conditions of practicum without modules. Meanwhile, the data analysis used in this research was qualitative data analysis, which involved summarizing the results of the interviews that had been described. Modules are highly essential in practicum because without modules, there would be no guidance when conducting a practicum. Modules are comparable to books that provide instructions before conducting practicum and also serve as a source of additional information related to the upcoming practicum.